Initiation of a Night Float System in an Otolaryngology Residency: Resident Perception and Impact on Operative Volume. (2nd April 2021) - Hamill, Chelsea S.; Cabrera, Claudia I; Murthy, Henna; Mowry, Sarah; Maronian, Nicole; Tamaki, Akina
Abstract : Objectives: Evaluate resident perception on implementation of a night float (NF) system to an otolaryngology residency program. We compared these perceptions to Accreditation Council for Graduate Medical Education (ACGME) case log data. Methods: A retrospective anonymous survey was sent to residents and alumni graduating between 2015 and 2023. Deidentified ACGME case log information was then examined for key indicator (KI) cases from post graduate year (PGY) 2 and PGY5. Results: Thirty (93.8%) residents and alumni responded. Residents with NF answered more positively compared to those without NF on following duty hour violations: 80‐hour work week, 1‐in‐7 days off, 1 call every 3 days, adequate time between shifts, and allotted time after a 24‐hour shift. Residents most commonly agreed that NF has improved patient care, resident education, and resident morale. Although residents with NF were neutral on PGY2 case volume effects, they disagreed that it affected overall case volume. The only KIs that differed for both PGY2 and PGY5s were airway cases ( P = .004 vs P = .002) and bronchoscopy ( P = .02 vs P = .006), which were significantly higher for those with NF. Thyroid surgery was the only KI higher for the residents without NF and spanned all PGY levels. Conclusion: Residents and alumni agreed that NF implementation had a positive effect on duty hour violations. The NF system does not have significant impact on case volume. Level of Evidence: 4 Laryngoscope, 131:2211–2218, 2021